Analisis Hukum Penerapan Restorative Justice Tindak Pidana Korupsi Dengan Nilai Kerugian Dibawah 50 Juta - Barita, Fahmi Ibnu; Saefudin, Yusuf (UMPurwokerto Law Review, 2024)
Abstract This study discusses restorative justice associated with corruption cases of under 50 million. Criminal acts of corruption in Indonesia have developed in such a way that they are both carried out by individuals and congregations in a systemic way. Cases of criminal acts of corruption to seek compensation for small-scale state losses, restorative justice is an approach that seeks to resolve criminal acts peacefully by empowering parties who have an interest in resolving these criminal cases. This peaceful settlement can occur if the perpetrator is aware of awareness and is voluntarily willing to provide compensation to the victim. This research concludes with the formulation of the problem, the first is the legal basis regarding the application of restorative justice in criminal acts of minor corruption and the second is a legal analysis of the application of restorative justice in criminal acts of minor corruption. This research method is a normative juridical method and the results of this study are that minor corruption cases still use restorative justice which refers to the prosecutor’s regulation number 15 of 2020 concerning termination of prosecution based on restorative justice. Where the perpetrators of corruption only return the money they corrupted. Â Keywords: restorative justice,minor acts of corruption, judiciary Â Abstrak Penelitian ini membahas mengenai restorative justice yang diakitkan dengan kasus tindak pidana korupsi dibawah 50 juta. Tindak pidana korupsi di indoneisa tela berkembang sedemikian rupa baik yang dilakukan oleh perorangan maupun berjamaah dengan cara sistemik. Perkara tindak pidana korupsi untuk mengupayakan pengambalian kerugaian negra berskala kecil, restorative justice merupakan pendekatan yang berupaya untuk menyelesaikan tindak pidana secara damai dengan pemberdayaan pada pihak yang memiliki kepentingan dalam penyelesaian perkara tindak pidana tersebut. Penyelesaian secara damai tersebut dapat terjadi apabila pelaku menyadari kesadaran dan dengan sukarela bersedia memberi ganti kerugian pada korban. Penelitian ini disimpulkan rumusan masalah yang pertama landasan hukum tentang penerapan restorative justice dalam tindak pidana kasus korupsi ringan dan yang kedua analisis hukum terhadap penerapan restorative justice dalam tindak pidana korupsi ringan. Metode penelitian ini merupakan metode yuridis normative dan hasil penelitian ini adalah kasus korupsi ringan tetap mengguanakan restorative justice yang merujuk pada peraturan jaksa nomor 15 tahun 2020 tentang penghentian penuntutan berdasarkan keadilan restorative. Yang dimana pelaku korupsi hanya mengembalikan uang yang dikorupsinya. Â Kata kunci:restorative justice, tindak pidana korupsi ringan, kejaksaan